Natural immunity and protection against variants in South African children through five COVID-19 waves: A prospective study - Heather J. Zar; Lesley Workman; Rae MacGinty; Maresa Botha; Marina Johnson; Adam Hunt; Tiffany Burd; Mark P. Nicol; Stefan Flasche; Billy J. Quilty; David Goldblatt (International Journal of Infectious Diseases)
Objectives: Children have been largely spared from serious disease through the COVID-19 pandemic despite a high exposure to SARS-CoV-2. Antibody responses to exposure and their role in protecting children from subsequent variant infection remain poorly understood. Methods: This is a prospective cohort study of children in a South African community through ancestral/Beta/Delta/Omicron BA.1/BA.2 and BA.4/BA.5 SARS-CoV-2 waves (March 2020-October 2022). Health seeking behavior/illness was recorded and postwave serum samples measured for immunoglobulin (Ig) G to spike (S) (CoV2-S-IgG) by electrochemiluminescent immunosorbent assay. To estimate the protective CoV2-S-IgG threshold levels, logistic functions were fit to describe the correlation of CoV2-S-IgG measured before a wave and the probability for seroconversion/boosting thereafter. Results: Despite little disease, 125 per 366 (34.2%) children (median age 6.7 years [interquartile range 5.99-7.4 years]) were seropositive after wave I, rising to 53.6%, 76.0%, and 96.2% and 99.2% after waves II (Beta), III (Delta), and IV and V (Omicron variants), respectively. CoV2-S-IgG induced by natural exposure protected against subsequent SARS-CoV-2 infection, with the greatest protection for Beta and least for Omicron. The levels of IgG specific for ancestral S antigen that provided a 50% protective threshold for the subsequent wave were lowest for the Beta and highest for the Omicron BA.1/BA.2 wave. In the multivariate analysis, maternal seropositivity (adjusted odds ratio = 2.57 [95% confidence interval: 1.72-3.82]) was strongly associated with child seropositivity. Conclusion: Children responded robustly to successive waves of SARS-CoV-2, mounting IgG responses to S antigen that were protective against subsequent waves. In the absence of vaccination, almost all children were seropositive after wave V but none were hospitalized, suggesting that natural immunity alone may be sufficient to protect children in a pandemic setting.